Pelanggaran Kode Etik Hakim Mahkamah Konstitusi dan Implikasinya Terhadap Keabsahan Putusan MK Nomor 90/PUU-XXI/2023 - Julius, Tambok; Oktaviani, Eka Putri; Rianida, Puja; Thoriq, Ahmad Reihan; Shakira, Talitha Atha; M, Mulyadi (Media Hukum Indonesia (MHI), 2025)
The Constitutional Court (MK) has an important role in maintaining the supremacy of the constitution and ensuring that policies and regulations are in accordance with constitutional principles. As an institution authorized to examine laws, decide disputes between state institutions, and resolve disputes over election results, the Constitutional Court is required to act independently and with integrity. Therefore, MK judges must uphold professional ethics and codes of conduct so that public trust in their decisions is maintained. However, there have been allegations of ethical violations by judges in several cases. The method used in the research is normative juridical with data sources derived from literature review, journals, and legal regulations. The approach applied includes a statutory approach and a case approach. Data collection techniques are carried out through primary data that refers to applicable positive laws, as well as secondary data obtained from journals and other sources. The results obtained in this study are that the supervision mechanism applied by MKMK is tiered and strict, starting from preliminary examination to in-depth investigation, while still upholding the principle of presumption of innocence. Then, the validity of the decision of the Constitutional Court (MK) legally remains valid even though there is a violation of the code of ethics by the judge, as seen in MK Decision Number 90/PUU-XXI/2023 concerning the age limit of presidential candidates.